Penggunaan Model Pembelajaran Student Facilitator and Explaining untuk Meningkatkan Keterampilan Berbicara pada Siswa Kelas XI IPA 2 SMA Negeri 1 Pare-Pare: The Use of Student Facilitator and Explaining Learning Models to Improve Speaking Skills in Class XI IPA 2 Students of SMA Negeri 1 Pare-Pare - Ardani, R. Gymnastiar; Muliadi , Muliadi; Puspitasari, Andi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to improve students' speaking skills through the Student Facilitator And Explaining learning model on descriptive text learning materials for class XI IPA 2 students of SMA Negeri 1 Pare-pare. Students' speaking skills are still lacking because students are still not confident when speaking in class. The use of less interesting models can also make students bored in receiving learning materials. The type of research used is Classroom Action Research (CAR) which is carried out in the form of a cycle. Each cycle has four stages, namely, the planning, implementation, observation and reflection stages. The subjects in the study were 36 students of class XI IPA 2 at SMA Negeri 1 Pare-pare. In the process of learning to speak using the Student Facilitator And Explaining model in learning speaking skills has been successful. This is evidenced by the average value of student observations which increased, namely in cycle 1 the first meeting with a percentage of 42% then increased in the second meeting with a percentage of 50%. In cycle 2 the first meeting became 58% and in the second meeting of cycle 2 became 72% with a very good category. The results of the study on students' speaking ability showed an increase with the success indicator that must be achieved, namely 75% of students who get a Minimum Completion Criteria (KKM) score of 75. The learning outcomes in cycle I were with a percentage result of 44% or an average result of 73, different from cycle II which experienced more effective changes, namely with a percentage result of 78% or an average result of 83. In cycle II, students were more enthusiastic in participating in the learning.